1900
DOI: 10.1113/jphysiol.1900.sp000821
|View full text |Cite
|
Sign up to set email alerts
|

The immediate action of an intravenous injection of blood‐serum

Abstract: and the Royal College of Surgeons, England.)IN carrying out some experiments with antitoxic serum I was surprised to find that the intravenous injection of diluted blood-serum into a cat produced a marked effect upon the heart and respiration.As serum is now being extensively used for therapeutic purposes I thought it would be well to follow this observation further. At the outset I must mention, that of the animals tested, dog, cat and rabbit, the effect is only to be observed in the cat. A second important p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1944
1944
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The toxic actions of serum in cats were in other animals. first examined by Brodie (1900). His records of the changes occurring in blood pressure and SUMMARY respiration are undistinguishable from the tracings we obtained with ATP.…”
Section: Discussionmentioning
confidence: 63%
“…The toxic actions of serum in cats were in other animals. first examined by Brodie (1900). His records of the changes occurring in blood pressure and SUMMARY respiration are undistinguishable from the tracings we obtained with ATP.…”
Section: Discussionmentioning
confidence: 63%
“…Brodie (4) was the first to describe a complex cardiorespiratory response, which included bradycardia, hy-potension, and apnea followed by rapid, shallow breathing and bronchoconstriction, after IV injection of horse serum in cats. Since then, various chemicals, including phenyl diguanide, capsaicin (8), and lactic acid (20,22), have been shown to evoke a PCR in numerous species, including conscious adult sheep (7).…”
Section: Pcrmentioning
confidence: 99%
“…The fact that defibrinogenated blood increased vascular tone in perfused dog muscle was first reported by Ludwig and Schmidt (1868) , and Page (1954) also quoted a paper by LT Stevens and FS Lee, who in 1884 reported the existence of a vasoconstrictive substance in clotted blood. This finding was supported by the later work of TG Brodie, the Director of the combined laboratories of the Royal College of Physicians and Royal College of Surgeons in London, who observed that preventing blood from clotting, by adding sodium citrate, also prevented the action of the vasoconstrictive substance ( Brodie, 1900 , 1903 ). Subsequent attempts were made to identify the substance further by examining whether it was heat stable and dialysable, but many of the data were conflicting and have been reviewed in detail elsewhere ( Page, 1954 ).…”
Section: The Characterization and Identification Of 5‐htmentioning
confidence: 77%